Circularly polarised solar antenna for airborne communication nodes. Issue 9 (1st April 2015) - O'Conchubhair, O.; Narbudowicz, A.; McEvoy, P.; Ammann, M.J.
Abstract : A circularly polarised solar cell antenna consisting of four sequentially rotated printed inverted‐F antennas is proposed. Four multicrystalline silicon solar cells act as the ground plane and the antenna is suitable for low‐power airborne communication nodes and wireless sensor networks. The antenna design was developed to allow 100% insolation of the cells when directly facing a light source. The low‐profile antenna minimises shadowing of the solar cell for oblique angle insolation.